Nanoimprint Technology : Nanotransfer for Thermoplastic and Photocurable Polymers. - Taniguchi, Jun (Microsystem and Nanotechnology Series??(ME20), 2013)
Nanoscale pattern transfer technology using molds is a rapidly advancing area and one that has seen much recent attention due to its potential for use in nanotechnology industries and applications. However, because of these rapid advances, it can be difficult to keep up with the technological trends and the latest cutting-edge methods. In order to fully understand these pioneering technologies, a comprehensive understanding of the basic science and an overview of the techniques are required. Nanoimprint Technology: Nanotransfer for Thermoplastic and Photocurable Polymers covers.